Implementasi STBI “Search Operation” dalam Meningkatkan Literasi Informasi Mahasiswa dalam Pembelajaran Daring - Ratih Desnita Wilanda (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2021)
Information literacy ability is very important possessed by students. It is intended that the information needed can be met properly. This article will discuss the implementation of the STBI "Search Operation" to help students find information according to their needs. This also relates to the online learning process. This article uses a qualitative method using descriptive analysis method. The purpose of this article is to assist students in implementing STBI "Search Operations" and provide an understanding of the effects of "Search Operations" in the online learning process and improve student literacy skills.